Intravoxel incoherent motion (IVIM) modeling of diffusion MRI during chemoradiation predicts therapeutic response in IDH wildtype glioblastoma. (March 2021) - Jabehdar Maralani, Pejman; Myrehaug, Sten; Mehrabian, Hatef; Chan, Aimee K.M.; Wintermark, Max; Heyn, Chris; Conklin, John; Ellingson, Benjamin M.; Rahimi, Saba; Lau, Angus Z; Tseng, Chia-Lin; Soliman, Hany; et al.
Highlights: Simplified IVIM metrics from MRIs taken during chemoradiation have prognostic value. Nonenhancing T2-FLAIR regions have important prognostic value. Abstract: Background: Prediction of early progression in glioblastoma may provide an opportunity to personalize treatment. Simplified intravoxel incoherent motion (IVIM) MRI offers quantitative estimates of diffusion and perfusion metrics. We investigated whether these metrics, during chemoradiation, could predict treatment outcome. Methods: 38 patients with newly diagnosed IDH-wildtype glioblastoma undergoing 6-week/30-fraction chemoradiation had standardized post-operative MRIs at baseline (radiation planning), and at the 10th and 20th fractions. Non-overlapping T1-enhancing (T1C) and non-enhancing T2-FLAIR hyperintense regions were independently segmented. Apparent diffusion coefficient (ADCT1C, ADCT2-FLAIR ) and perfusion fraction ( f T1C, f T2-FLAIR ) maps were generated with simplified IVIM modelling. Parameters associated with progression before or after 6.9 months (early vs late progression, respectively), overall survival (OS) and progression-free survival (PFS) were investigated. Results: Higher ADCT2-FLAIR at baseline [Odds Ratio (OR) = 1.06, 95% CI 1.01–1.15, p = 0.025], lower f T2-FLAIR at fraction 10 (OR = 2.11, 95% CI 1.04–4.27, p = 0.018), and lack of increase in ADCT2-FLAIR at fraction 20 compared to baseline (OR = 1.12, 95% CI 1.02–1.22, p = 0.02) were associated with early progression. Combining ADCT2-FLAIR at baseline, f T2-FLAIR at fraction 10, ECOG and MGMT promoter methylation status significantly improved AUC to 90.3% compared to a model with only ECOG and MGMT promoter methylation status ( p = 0.001). Using multivariable analysis, neither IVIM metrics were associated with OS but higher f T2-FLAIR at fraction 10 (HR = 0.72, 95% CI 0.56–0.95, p = 0.018) was associated with longer PFS. Conclusion: ADCT2-FLAIR at baseline, its lack of increase from baseline to fraction 20, or f T2-FLAIR at fraction 10 significantly predicted early progression. f T2-FLAIR at fraction 10 was associated with PFS.